PENGEMBANGAN KARIR DAN PENGENDALIAN INTERNAL DALAM RANGKA MENINGKATKAN KINERJA PELAYANAN PUBLIK (Studi di Rumah Sakit Daerah Puri Husada Tembilahan Kabupaten Indragiri Hilir) - jurnalmap map; Asnawi ÔÇÄ; Hadi Susanto; Sri Mulyani (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2020)
This study aims to describe the effect of career development, career commitment and internal control on the performance of public services partially or simultaneously at Puri Husada Tembilahan District Hospital. The study population included all employees of Puri Husada Tembilahan Regional Hospital totaling 218 people, taken as many as 141 employees. Data collection is done by questionnaire. Then the data were analyzed with multiple regression analysis techniques. The results showed that partially career development, career commitment and internal control significantly influence the performance of public services. Career Development is the dominant variable influencing the performance of public services at RSUD Puri Husada Tembilahan. Simultaneously career development, career commitment and internal control significantly influence the performance of public services. Organizational goals will be easily achieved if the organization can develop career and career commitments for employees and improve internal control so as to improve the performance of public services. Keywords: performance, public services, career, internal control